Differentiation of ureteral stones and phleboliths using Hounsfield units on computerized tomography: a new method without observer bias - ŞEKERCİ, ÇAĞRI AKIN; ŞİMŞEK, FERRUH; TİNAY, İLKER; ŞENER, TARIK EMRE; TANIDIR, YILÖREN (SPRINGER, 2017)
To differentiate ureteral stones and phleboliths by measuring density [as Hounsfield unit (HU)] and volume (as mm(3)) of the opacities in the bony pelvis on unenhanced computerized tomography (U-CT). A total of 52 patients, who underwent semirigid ureteroscopy and laser lithotripsy for distal ureteral stone and had isochoronous phleboliths in U-CT, were included. Images were reviewed for density and volume of the opacities. Data were compared, and a cut-off value was defined with receiver operating characteristics curve analysis to differentiate the nature of the opacity. Using the cut-off values of 171 mmA(3) for volume (sensitivity 75 %, specificity 100 %) and 643 HU for density (sensitivity 75 %, specificity 93 %), differentiation between stone and phlebolith was achieved. Differentiation of pelvic opacities needs meticulous observation with certain signs on U-CT. On the other hand, our study offers a new method, with certain cut-off values, such as 643 HU and 171 mm(3), which can be used to precisely predict the actual nature of opacities of interest.
Keywords: Diagnosis; Imaging; Hounsfield unit; Ureteral stones; Ureteroscopy; UNENHANCED HELICAL CT; DUAL-ENERGY CT; DISTINGUISHING PELVIC PHLEBOLITHS; TRACT STONE; CALCULI; URETEROSCOPY; MANAGEMENT; DIAGNOSIS; UROGRAPHY; PROTOCOL